Quantifying production, processing and post-slaughter effects on pork eating quality using random effects meta-regression - Channon, H. A. (Transl Anim Sci, 2017)
Random effects meta-regression techniques, analyzed using a restricted maximum likelihood (REML) approach, was used to determine the influence of various factors that may be experienced or imposed on pigs, carcases and pork on pork eating quality attributes and shear force of the M. longissimus dorsi (loin). This was done to inform the development of a pathway based eating quality system for pork. Estimated means of explanatory variables were obtained for those pathway factors where sufficient published studies met the criteria for inclusion in the analysis. Due to a lack of data for interactions between factors investigated, only single factors were included as fixed terms in the REML models. This analysis identified that moisture infusion (P < 0.001), ageing for more than 2 d post-slaughter (P = 0.006) and tenderstretching (P = 0.006) each resulted in significant improvements in tenderness. Cooking loins to an endpoint temperature of ≥ 80°C negatively impacted both tenderness (P = 0.022) and juiciness (P < 0.001) scores compared with 70 to 74°C. It was not possible to develop algorithms to reliably estimate the effects of multiple factors on pork eating quality attributes to a cuts-based level due to limited studies reporting data for treatment interactions.